2020
DOI: 10.1007/s10123-020-00135-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different culture media for detection and quantification of H. pylori in environmental and clinical samples

Abstract: The objective of the present study was to establish the most suitable culture medium for the isolation of H. pylori from environmental and clinical samples.Ten different culture media were compared and evaluated. Four of them had been previously described and were modified in this study. The rest of the media were designed de novo. Three different matrices, tap water, wastewater, and feces, were inoculated with serial dilutions of H. pylori NCTC 11637 strain at a final concentration of 10 4 and 10 3 CFU/ml and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Azevedo et al ( 37 ) noticed that the media which are too rich in nutrients may also cause a nutritional shock and prevent the growth of the bacteria. Thus, some of the authors are focused on evaluating different types of culture media for the detection and quantification of H. pylori in environmental samples ( 20 ). Besides the modifications in culture media, selective separation techniques like immunomagnetic beads for selective isolation of H. pylori were also applied based on the immunological properties of the bacterium.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Azevedo et al ( 37 ) noticed that the media which are too rich in nutrients may also cause a nutritional shock and prevent the growth of the bacteria. Thus, some of the authors are focused on evaluating different types of culture media for the detection and quantification of H. pylori in environmental samples ( 20 ). Besides the modifications in culture media, selective separation techniques like immunomagnetic beads for selective isolation of H. pylori were also applied based on the immunological properties of the bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the disadvantages of culture techniques for the detection of VBNC forms of pathogens, this technique is the gold-standard method to detect viable H. pylori from environmental media when compared with molecular techniques. Furthermore, bacteria isolation is important for epidemiological and antimicrobial sensitivity analysis ( 20 ). Hortelano et al ( 20 ) suggested the optimization of cultivations techniques is essential for the isolation of H. pylori from environmental samples.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cultivation of H. pylori depends on the quality of biopsy samples, the delayed transport, exposure to the aerobic environment, and other factors, but it is essential for testing for susceptibility to antibiotics [ 58 , 59 , 60 , 61 ]. Host factors like low bacterial load, use of PPIs, antibiotics, alcohol, and bleeding can change the culture-positive rate.…”
Section: Current Diagnostic Methodsmentioning
confidence: 99%